Mixing Time Optimization of Chitosan-Bentonite Composites for Sustainable Clay Liner Applications - Arifin, Yulian Firmana; Rusdiansyah, Rusdiansyah; Adriani, Adriani; Arfiandoyo, Muhammad Nur; Rizqullah, Muhammad Naufal Herfian (Engineering, Technology & Applied Science Research, 2025)
Bentonite-chitosan composites offer promising potential as clay liners due to their low permeability and enhanced mechanical properties. However, the extended mixing times required for optimal composite performance pose challenges for large-scale applications. This study investigates the effects of varying mixing times on the properties of bentonite-chitosan composites to optimize their performance while improving practicality. The composites were prepared by mixing bentonite with chitosan in acetic acid and sodium tripolyphosphate (STPP) solutions for varying durations. Characterization tests, including FTIR, TGA, and SEM-EDX, were conducted to assess the chemical interactions, thermal stability, and morphology. The plasticity was evaluated through the Liquid Limit (LL) and Plasticity Index (PI), while the permeability was tested using the falling head method at 16 kN/m³ density and 10% water content. The results indicated that longer mixing times, particularly 2 hours in acetic acid and 4 hours in STPP, resulted in the lowest permeability (1×10⁻¹² m/s) and the best structural integrity. However, shorter mixing times, such as 2 hours in acetic acid and 2 hours in STPP, also provided acceptable performance, offering a practical alternative. Pure bentonite, while exhibiting low permeability, lacked the structural integrity achieved by chitosan-enhanced composites. Future research should focus on evaluating the long-term durability of these composites under field conditions, their scalability, and performance in sand-bentonite mixtures, emphasizing the role of optimized mixing times in improving composite performance.